Carbon emissions embodied in Russia's trade - Igor A. Makarov; Anna K. Sokolova (FIW - Research Centre International Economics, 2015)
According to current international climate change regime countries are responsible for greenhouse gas (GHG) emissions, which result from economic activities within national borders, including emissions from producing goods for exports. At the same time imports of carbon intensive goods are not regulated by international agreements. In this paper emissions embodied in exports and imports of Russia were calculated with the use of inter-country input-output tables. It was revealed that Russia is the second largest exporter of emissions embodied in trade and the large portion of these emissions is directed to developed countries. The reasons for high carbon intensity of Russia's exports are obsolete technologies (in comparison to developed economies) and the structure of commodity exports. Because of large amount of net exports of carbon intensive goods the current approach to emissions accounting does not suit interests of Russia. On the one hand, Russia, as well as other large net emissions exporters, is interested in the revision of allocation of responsibility between producers and consumers of carbon intensive products. On the other hand, current technological backwardness makes Russia vulnerable to the policy of carbon protectionism, which can be implemented by its trade partners.
Keywords: F18; F64; Q65; 330; global climate change; carbon emissions; virtual carbon; carbon intensity of trade; Russia's trade; input-output analysis; Kyoto protocol